Bead-Based Hydrodynamic Simulations of Rigid Magnetic Micropropellers - Codutti, Agnese; Bachmann, Felix; Faivre, Damien; Klumpp, Stefan (Frontiers in Robotics and AI, 2018)
The field of synthetic microswimmers, micro-robots moving in aqueous environments, has evolved significantly in the last years. Micro-robots actuated and steered by external magnetic fields are of particular interest because of the biocompatibility of this energy source and the possibility of remote control, features suited for biomedical applications. While initial work has mostly focused on helical shapes, the design space under consideration has widened considerably with recent works, opening up new possibilities for optimization of propellers to meet specific requirements. Understanding the relation between shape on the one hand and targeted actuation and steerability on the other hand requires an understanding of their propulsion behavior. Here we propose hydrodynamic simulations for the characterization of rigid micropropellers of any shape, actuated by rotating external magnetic fields. The method consists of approximating the propellers by rigid clusters of spheres. We characterize the influence of model parameters on the swimming behavior to identify optimal simulation parameters using helical propellers as a test system. We then explore the behavior of randomly shaped propellers that were recently characterized experimentally. The simulations show that the orientation of the magnetic moment with respect to the propeller's internal coordinate system has a strong impact on the propulsion behavior and has to be known with a precision of ≤ 5° to predict the propeller's velocity-frequency curve. This result emphasizes the importance of the magnetic properties of the micropropellers for the design of desired functionalities for potential biomedical applications, and in particular the importance of their orientation within the propeller's structure.